Analisa Sistem Inference Fuzzy Sugeno Dalam Menentukan Harga Pembelian Tanah Untuk Pembangunan Komplek Perumahan Diwilayah Kutacane Aceh Tenggara - Rahmat Rahmat (STMIK Budi Darma, 2019)
Expert System (Expert System) is an information system that contains knowledge from an expert who has the knowledge, research, experience, special methods, and the ability to apply certain talents in their fields in solving problems that are applied to a system so that it can be used for consultation. Expertise (expertise) is extensive and specific knowledge obtained through a series of training, reading, and experience. Expert systems can also be used to help an expert or the general public to solve their problems in certain cases. One of the factors that causes failure is the maximum application of information technology. One of the uses of this technology is the use of expert systems. Given the importance of the value of a result to be saved because it is very useful for buyers, it is necessary to create a knowledge-based expert system that uses the Sugeno fuzzy method. Expert systems should be equipped with facilities that can provide certainty about system output. Many ways can be used to calculate the value of system output uncertainty. However, in this study it is necessary to make a knowledge-based expert system that uses the Sugeno fuzzy method by calculating the value to find the value with the previous case. Based on the tests carried out, it can be seen that fuzzy is able to produce the response as expected, namely being able to determine the area that has land suitable for building a housing complex.